THE ROLE OF DIGITAL MEDIA IN UNDERSTANDING INDONESIAN VOCABULARY IN THE ERA OF REVOLUTION 4.0 - Gumgum Gumilar; Ali Imron Al Ma'ruf; Harun Joko Prayitno; Minsih Minsih (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
The development of information and communication technology has changed the learning paradigm, especially in Indonesian vocabulary comprehension. Digital media, such as learning apps, educational websites and social media platforms, have become central entities in shaping and developing vocabulary comprehension. This study uses a qualitative method to analyze the role of digital media in the context of Indonesian vocabulary learning. Types of digital media are the subject of this study. The purposive sampling technique is a sampling method based on consideration. The data collection techniques used are documentation note-taking and listening techniques. Data sources are based on national data on certain websites and research articles. Data validation uses data triangulation, sources and techniques. While the data analysis technique is by collecting, reducing, presenting, and drawing conclusions from the data. The results show that digital media accelerates access to information, providing diverse learning options. Social media and online communities also play a role in facilitating language learning through discussion and information sharing. Educational video-based digital media, such as online tutorials, create a holistic learning experience through the audiovisual dimension. Technology learning platforms, such as Duolingo and Quizlet provide structured exercises to enrich vocabulary while online dictionaries and translation services facilitate quick and effective vocabulary comprehension. This research is expected to provide further understanding on how digital media can be optimally integrated in Indonesian vocabulary learning in the era of revolution 4.0. It is also hoped that digital media users can choose a platform that suits the learning material and select quality educational content.